2015
DOI: 10.1590/s0100-204x2015001100012
|View full text |Cite
|
Sign up to set email alerts
|

Fertilidade do solo e estado nutricional do cafeeiro cultivado em atmosfera enriquecida com CO2

Abstract: Resumo -O objetivo deste trabalho foi avaliar os efeitos de concentrações de CO 2 atmosférico nos atributos químicos do solo, na linha (cafeeiro) e na entrelinha (braquiária), e nos teores de macronutrientes em folhas do cafeeiro. Utilizou-se o delineamento de blocos ao acaso, com parcelas subdivididas e seis repetições. Os tratamentos consistiram de dois níveis de CO 2 atmosférico, 390 e 550 μmol mol , K, P e S disponíveis, saturação por bases e matéria orgânica do solo. Em 2013 e 2014, houve redução nos teor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
3
0
2
Order By: Relevance
“…Similar results were obtained by Maluf et al (2015) and by Flori and Resende (2016). Maluf et al (2015) found in the coffee area, both at 0-0.1m and 0.1-0.2m soil layers, higher values of pH, organic matter, Ca 2+ , Mg 2+ and row saturation than in the transplant line, in the fertilizer strip. Flori and Resende (2016) obtained, at 0-0.2m soil layer, higher levels of organic matter, P and Ca 2+ between rows in relation to the banana plantation row.…”
Section: Methodssupporting
confidence: 88%
“…Similar results were obtained by Maluf et al (2015) and by Flori and Resende (2016). Maluf et al (2015) found in the coffee area, both at 0-0.1m and 0.1-0.2m soil layers, higher values of pH, organic matter, Ca 2+ , Mg 2+ and row saturation than in the transplant line, in the fertilizer strip. Flori and Resende (2016) obtained, at 0-0.2m soil layer, higher levels of organic matter, P and Ca 2+ between rows in relation to the banana plantation row.…”
Section: Methodssupporting
confidence: 88%
“…Martins et al (2014) avaliaram o efeito combinado do aumento da concentração de CO 2 e da temperatura e verificaram que, apesar das mudanças promovidas pelos dois fatores do ambiente, a maioria dos nutrientes foi mantida dentro de uma faixa considerada adequada, o que indica que a planta pode manter balanços minerais satisfatórios nos cenários climáticos futuros. Entretanto, em experimento do tipo Face, verificou-se que, em cafeeiros cultivados em atmosfera enriquecida com CO 2 , o teor de P disponível no solo é o que mais se reduz, e isto é indicativo da necessidade de reposição adequada deste nutriente (Maluf et al, 2015).…”
Section: Resultsunclassified
“…The CO 2 levels on the eCO 2 plots were kept within the target concentration for 60% of the experimental period. The soil is classified as dystrophic Red Latosol with clayey texture, according to the Brazilian soil classification (see Maluf, Ghini, Melo, & Silva, for soil fertility details). Soil is moderately acid with base saturation (V) of approximately 50% without high concentrations of aluminium, and its chemical characteristics were not significantly different among CON and eCO 2 plots (Table ).…”
Section: Methodsmentioning
confidence: 99%
“… Treatments: CON—ambient conditions (≈390 μmol/mol CO 2 ), eCO 2— CO 2 fertilization (≈550 μmol/mol CO 2 ); SB—sum of basis; CEC—cation exchange capacity; V—percentage of soil base saturation; OM—organic matter content. Adapted from Maluf et al (). …”
Section: Methodsmentioning
confidence: 99%